Bahrain's Economic Evolution: A Journey from the Oil Era to Sector Diversification - Riadhotul Muamalah; Imam Ghazali (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
As an island nation with limited oil reserves, Bahrain faces structural vulnerabilities rooted in its historical reliance on the hydrocarbon sector. This study analyses Bahrain’s economic diversification strategy focusing on finance, tourism, information technology, and SMEs through a qualitative approach grounded in the theoretical framework of New Institutional Economics (NIE). It evaluates how institutional reforms, such as Bahrain Economic Vision 2030 and regulatory sandboxes, alongside fiscal incentives (VAT and corporate tax), have driven structural transformation. The contribution of the non-oil sector to GDP has increased from 50% in 2000 to over 80% in 2023. Key successes include the growth of Islamic finance (16– 18% of GDP) and the expansion of SMEs (30% of GDP), supported by full foreign ownership policies and Tamkeen’s training programs. These sectors have generated employment while enhancing macroeconomic stability and fostering an innovation-driven ecosystem. Nevertheless, persistent challenges such as dependence on foreign labour (70% of the workforce), regional competition with Dubai and Saudi Arabia, and land limitations (786.5 km²) demand adaptive solutions. Theoretically, this study applies Douglass North’s concept of path dependence and Oliver Williamson’s transaction cost theory to understand institutional transitions in Gulf rentier states. Practically, it offers insights for policymakers in middle- income, resource-constrained economies seeking long-term diversification. The findings underscore the need for a holistic approach combining regulatory reform, human capital development, and targeted investment incentives to achieve sustainable post-oil economic transformation.